Pemetaan Tren Penelitian Etnomatematika Berbasis Budaya Melayu Riau dalam Pembelajaran Matematika: Sebuah Systematic Literature Review - Istiqomah; Afiah Syausan; Hilvi Lubabil; Kuni Reza; M. Hasan Asnawi (IEC: Journal of Educational Innovation, 2026)
Ethnomathematics has developed rapidly as a bridge between local cultural knowledge and formal mathematics learning in Indonesia; however, a systematic mapping of ethnomathematics research rooted in Riau Malay culture remains limited, even though Riau possesses rich cultural artifacts traditional houses, carvings, tabak, songket, cuisine, and traditional numeration systems that hold considerable potential as sources of contextual mathematics learning. This study aims to map the trends, characteristics, and thematic tendencies of ethnomathematics research based on Riau Malay culture in mathematics learning during the 2016–2026 period. A Systematic Literature Review (SLR) was conducted using a simplified PRISMA-based protocol, searching Google Scholar, DOAJ, and SINTA-indexed journal portals with the keywords “etnomatematika Melayu Riau,” “Riau culture mathematics,” and their English equivalents. After identification, screening, and eligibility assessment, 16 articles explicitly addressing Riau Malay ethnomathematics were obtained. The mapping results show that publications increased significantly after 2020 and peaked in 2024–2025; the objects of study were dominated by traditional house architecture (37.5%), followed by traditional cuisine and other cultural artifacts; the most targeted educational levels were elementary and junior secondary schools; and qualitative exploratory-ethnographic approaches still dominate over research and development (R&D) and quasi-experimental designs. This study also identifies a research gap in the limited integration of digital technology and the scarcity of studies at the senior secondary and higher education levels. In conclusion, Riau Malay ethnomathematics research shows a positive trend but remains thematically, methodologically, and geographically fragmented, necessitating a more integrated research agenda to strengthen its contribution to culturally grounded mathematical literacy.